2007
DOI: 10.1111/j.1440-1827.2007.02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased wild‐type p53‐induced phosphatase 1 (Wip1 or PPM1D) expression correlated with downregulation of checkpoint kinase 2 in human gastric carcinoma

Abstract: Phosphorylation of checkpoint kinase 2 (Chk2) at Thr68 (pChk2) induced by DNA double-strand breaks is required for inhibition of cell cycle progression in the G(2) phase. The purpose of the present paper was to investigate the expression of wild-type p53-induced phosphatase 1 (Wip1 or PPM1D), a negative regulator of Chk2, to better understand its role in human gastric cancer. In non-neoplastic gastric mucosa, most epithelial cells exhibited Wip1-positive and pChk2-negative immunoreactivity, whereas an inverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 21 publications
(28 reference statements)
0
42
0
Order By: Relevance
“…However, PPM1D amplification and/ or enhanced stabilization allow for sustained inhibition of DNA damage response proteins and numerous tumor suppressors, including ATM, Chk1 and 2, and p53. PPM1D over-expression has been implicated in a variety of human malignancies, including OVCA, and its level is directly related to poor prognosis and reduced therapeutic outcome [47][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…However, PPM1D amplification and/ or enhanced stabilization allow for sustained inhibition of DNA damage response proteins and numerous tumor suppressors, including ATM, Chk1 and 2, and p53. PPM1D over-expression has been implicated in a variety of human malignancies, including OVCA, and its level is directly related to poor prognosis and reduced therapeutic outcome [47][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Given that 17q23.2 was one of the most commonly amplified regions in HER-2-positive cancers (20%) and also found in luminal tumors (8%) and the fact that PPM1D has been shown to have oncogenic properties (33,34) and to be a protein amenable to targeting with small-molecule inhibitors (24), we investigated whether PPM1D would be one of the drivers of the 17q23.2 amplicon. PPM1D encodes a serine/threonine phosphatase and has been described previously as an oncogene and potential therapeutic target (24).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PPM1D also participates in the regulation of DNA repair via an interaction with UNG glycosylase (41), progesterone receptor function (42), and the regulation of CHK1, CHK2, and ATM kinases, which control DNA repair and cell cycle (43 -47). PPM1D overexpression has been shown to recapitulate the antiapoptotic effects of TP53 inactivating mutation in vitro and increases tumorigenicity in murine models in vivo (33,34). Recent studies have shown that inactivation of p38 due to PPM1D gene amplification and expression contributes to the development of human cancers by suppressing p53 activation (34).…”
Section: Discussionmentioning
confidence: 99%
“…Wip1 is closely associated with p53 (8). Wip1, which is overexpressed in numerous cancers, including breast cancer (19), medulloblastoma (20), pancreatic neuroendocrine tumor (21), liver cancer (22) and stomach cancer (23), is recognized as a novel oncogene inhibiting several p53-dependent tumor-suppressor signaling pathways, including the Ataxia telangiectasia mutated-checkpoint kinase 2-p53, p38 mitogen-activated protein kinase-p53 and nuclear factor-κB signaling pathways (19). Discher et al (14) reported that Wip1 was associated with the chemosensitivity of cancer, since downregulation of Wip1 gene expression could inhibit the self-proliferation of breast cancer stem cells and enhance the chemosensitivity of MCF-7 breast cancer cells to doxorubicin.…”
Section: Discussionmentioning
confidence: 99%